Epileptiform and periodic EEG activities induced by rapid sevoflurane anaesthesia induction. Issue 3 (March 2018) - Sonkajärvi, Eila; Rytky, Seppo; Alahuhta, Seppo; Suominen, Kalervo; Kumpulainen, Timo; Ohtonen, Pasi; Karvonen, Elina; Jäntti, Ville
Highlights: Rapid anaesthesia mask induction with sevoflurane readily produces paroxysmal epileptiform or periodic EEG activity. These patterns are among the most frequent iatrogenic epileptiform events. Controlled hyperventilation doubles the amount of paroxysmal EEG activity. Abstract: Objectives: The aim of the study was to compare the EEG findings and haemodynamic parameters of adult male patients while undergoing mask induction with sevoflurane anaesthesia with either controlled hyperventilation (CH) or spontaneous breathing (SB). Methods: Twenty male patients, aged 23–52 (mean 42) years were anaesthetized randomly with either spontaneous breathing or mild controlled hyperventilation via mask. EEG was recorded using a full 10–20 electrode set. Results: Anaesthesia induction with high inhaled concentrations of sevoflurane produced several epileptiform and periodic EEG patterns. CH doubled the amount of these EEG patterns compared to SB. Higher heart rate was recorded in the CH group. Conclusions: We describe a high incidence of paroxysmal EEG activity: epileptiform and generalized periodic discharges (GPDs) during rapid sevoflurane in nitrous oxide-oxygen mask induction in hyperventilated male patients. However these activities have no effect to the heart rate or the mean arterial pressure. Significance: The monitoring of GPDs and burst suppression patterns during rapid anaesthesia induction with sevoflurane provides possibility to study the effects of volatile anaesthetics in the healthy brain. In order to analyse the different sources of EEG patterns a wide-band multichannel EEG recording is necessary.